Literature review of lean, agile, resilient, green (LARG) in automotive manufacturing industry - Purba Humiras Hardi; Aisyah Siti; Hasibuan Sawarni; Jaqin Choesnul (BIO Web of Conferences)
The lean, agile, resilient, green (LARG) aspect approach that has been implemented by several industries globally, is an important indicator of industrial performance in the future. Comprehensive implementation of LARG is not easy, especially for companies with limited resources, because it requires the support of relatively expensive machine and equipment technology. Research examining the application of LARG in the manufacturing industry sector in general has been carried out by many researchers, but the tendency is for partial implementation, especially in the manufacturing industry. Along with the development of the Indonesian national automotive industry which continues to grow after the COVID19 Pandemic, each company needs to increase its competitiveness based on LARG with each of its indicators. This study conducted a literature review on the application of LARG aspects in the automotive industry. The purpose of this study is to analyze the implementation of the LARG approach in the automotive industry. The stages carried out in this study are: literature search from journal databases, filtering results based on keywords and criteria, systematic review of filtered papers to provide further understanding. The results of the literature review show that research on the application of LARG in the automotive industry is still carried out partially with dominant lean and green aspects. Meanwhile, the implementation of agile and resilient aspects tends to be limited.